Dampak Terjadi Risiko Terhadap Waktu Pada Proyek Infrastruktur Jalan di Provinsi Aceh - Hawari, Rifat Aditya; Hildayani, Cut Sitti Rafidatul; Mauliana, Risma (Universitas Teuku Umar, 2025)
Road infrastructure development projects are dynamic and inherently inherently risky, both small and large-scale. Each project faces different risks and can impact its implementation. Therefore, risk assessment is essential to identify potential risks and mitigate potential negative impacts. The purpose of this study was to analyze the impact of risk on time (risk severity) in the implementation of road infrastructure projects in Aceh Province in 2021. The method used was a time-risk impact analysis method, with primary research sources obtained from questionnaire responses and secondary data obtained from literature studies. The respondents were from contractor companies, including: Directors (directors/deputy directors), Project Managers/Field Managers, and Engineers. Instrument validity and reliability tests were conducted in previous studies, while data processing was performed using descriptive statistical analysis and Severity Index (SI) analysis. The results of this study are expected to determine the impact of risk on time and the dominant variables in the implementation of road infrastructure development projects in Aceh Province.